Students' Mathematical Creative Thinking Skills in Solving The System of Two Variable Linear Equations Viewed From Gender - Maulida, Jumrotun; Khotimah, Rita Pramujiyanti (Universitas Wiralodra, 2023)
This study aims to describe students' mathematical creative thinking skills in solving two-variable linear equation system problems. Creative thinking skills used include 4 indicators, namely: 1) fluency, 2) flexibility, 3) originality, and 4) elaboration. This research is a qualitative descriptive study. Data collection techniques used in research are creative thinking tests, interviews, and documentation. The subjects of this study were six students from 8th grade of junior high student 1 Jelai who were selected based on high, medium, and low categorization. Data analysis techniques include data reduction, presentation, and conclusion. Test the validity of the data using technical triangulation. The research results are students in the high category can master the indicators of creative thinking from the four test questions. Students in the medium and low categories have not mastered all indicators of creative thinking on the four test questions. Students in the medium male category were able to master the fluency indicator in the first question, but in the second item they were not able to master the flexibility indicator, and in the third item they were able to master the originality indicator while in the fourth item, they were not able to master the elaboration indicator. Students in the low male category in questions one to three were unable to master the indicators of fluency, flexibility, and originality, while in the fourth item, they were able to master the Elaboration indicator. Students in the female category were able to master the fluency indicator on the first question, originality on the third question, and, elaboration on the fourth question, but on the second question, they were not able to master the flexibility indicator. Students in the low female category were able to master the indicators of fluency in the first question, but in the second, third, and fourth questions, they were not able to master the indicators of flexibility, originality, and elaboration.